Fully transparent metamaterial AMC backed CPW fed monopole antenna for IoT applications - Bui, Cong Danh; Desai, Arpan; Nguyen, Thi Thanh Kieu; Nguyen, Truong Khang (Vietnam Journal of Science and Technology, 2021)
In this paper, a fully transparent antenna comprising of an Artificial Magnetic Conductor (AMC) backed Co-planar Waveguide (CPW) fed dual-ring monopole is presented. The monopole antenna and AMC structure achieve transparency due to the use of AgHT-8 conductive oxide and Plexiglas substrate. Measured antenna performance shows an impedance bandwidth of 5.3 – 6 GHz (12.4%) in the U-NII-1 to U-NII-4 frequency band with a peak gain of 5.7 dBi which is approximately an increase of 4.5% and 3.9 dBi, respectively, as compared to the standalone antenna. The simulation and the measurement results agree well with each other which proves the validity of the proposed design. To the best of our knowledge, the proposed antenna is the first fully transparent antenna design combining a transparent radiator and a transparent AMC structure.